1991
DOI: 10.1017/s0022112091000630
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the dynamics and acoustics of travelling bubble cavitation

Abstract: Individual travelling cavitation bubbles generated on two axisymmetric headforms were detected using a surface electrode probe. The growth and collapse of the bubbles were studied photographically, and these observations are related to the pressure fields and viscous flow patterns associated with each headform. Measurements of the acoustic impulse generated by the bubble collapse are analysed and found to correlate with the maximum volume of the bubble for each headform. These results are compared to the obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
91
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(110 citation statements)
references
References 29 publications
19
91
0
Order By: Relevance
“…Blake et al (1977) photographed the collapse of cavitation bubbles over a tripped hydrofoil and observed that the bubble deforms into a hemispherical shape before collapsing and that it breaks up into pieces during the collapse process. A similar pattern of bubble breakup has been observed photographically in travelling bubble cavitation around axisymmetric headforms by Ceccio & Brennen (1991). Van der Meulen & van Renesse (1989) have acoustically and photographically studied the collapse of laser-produced cavities in flows around hemispherical headforms.…”
Section: Usasupporting
confidence: 56%
See 4 more Smart Citations
“…Blake et al (1977) photographed the collapse of cavitation bubbles over a tripped hydrofoil and observed that the bubble deforms into a hemispherical shape before collapsing and that it breaks up into pieces during the collapse process. A similar pattern of bubble breakup has been observed photographically in travelling bubble cavitation around axisymmetric headforms by Ceccio & Brennen (1991). Van der Meulen & van Renesse (1989) have acoustically and photographically studied the collapse of laser-produced cavities in flows around hemispherical headforms.…”
Section: Usasupporting
confidence: 56%
“…The bubble may break up during the collapse due to shear in the flow or as a result of the onset of large bubble oscillations. From the photographs of Ceccio (1990) one can estimate the two pieces to be 1 mm apart which, at a flow velocity of about 10 ms, would lead to peaks roughly 0.1 ms apart. This is substantially larger than the observed peak separation of about 0.015 ms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations